Global insights into the genome dynamics of Clostridioides difficile associated with antimicrobial resistance, virulence, and genomic adaptations among clonal lineages - Sholeh, Mohammad; Beig, Masoumeh; Kouhsari, Ebrahim; Rohani, Mahdi; Katouli, Mohammad; Badmasti, Farzad (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundClostridioides difficile is a significant cause of healthcare-associated infections, with rising antimicrobial resistance complicating treatment. This study offers a genomic analysis of C. difficile, focusing on sequence types (STs), global distribution, antibiotic resistance genes, and virulence factors in its chromosomal and plasmid DNA.MethodsA total of 19,711 C. difficile genomes were retrieved from GenBank. Prokka was used for genome annotation, and multi-locus sequence typing (MLST) identified STs. Pan-genome analysis with Roary identified core and accessory genes. Antibiotic resistance genes, virulence factors, and toxins were detected using the CARD and VFDB databases, and the ABRicate software. Statistical analyses and visualizations were performed in R.ResultsAmong 366 identified STs, ST1 (1,326 isolates), ST2 (1,141), ST11 (893), and ST42 (763) were predominant. Trends of genome streamlining included reductions in chromosomal length, gene count, protein-coding genes, and pseudogenes. Common antibiotic resistance genes—cdeA (99.46%), cplR (99.63%), and nimB (99.67%)—were nearly ubiquitous. Rare resistance genes like blaCTX-M-2, cfxA3, and blaZ appeared in only 0.005% of genomes. Vancomycin susceptibility-reducing vanG cluster genes were detected at low frequencies. Virulence factors showed variability, with highly prevalent genes such as zmp1 (99.62%), groEL (99.60%), and rpoB/rpoB2 (99.60%). Moderately distributed genes included cwp66 (54.61%) and slpA (79.02%). Toxin genes tcdE (91.26%), tcdC (89.67%), and tcdB (89.06%) were widespread, while binary toxin genes cdtA (26.19%) and cdtB (26.26%) were less common. Toxin gene prevalence, particularly tcdA and tcdB, showed a gradual decline over time, with sharper reductions for cdtA and cdtB. Gene presence patterns (GPP-1) for resistance, virulence, and toxin genes were primarily linked to ST2, ST42, and ST8.ConclusionThis study highlights C. difficile’s adaptability and genetic diversity. The decline in toxin genes reflects fewer toxigenic isolates, but the bacterium’s increasing preserved resistance factors and virulence genes enable its rapid evolution. ST2, ST42, and ST8 dominate globally, emphasizing the need for ongoing monitoring.